Homeopathic Remedies of Indian Origin in Hair Care (Homoeopathy for All, 2024)
In the contemporary era, where  personal presentation is intertwined  with professional and social success,  hair health has emerged as more than  a routine concern; it's a reflection of  one's lifestyle and well-being. Issues  like hair fall, dandruff, and early  graying, while common, carry an  emotional weight, impacting one’s  self-image and societal perception.  Hair, in many cultures, is a symbol  of vitality and youth, making its  care pivotal in the broader spectrum  of holistic health. This quest for  healthy hair often leads individuals  down the path of numerous cosmetic  treatments. While these solutions are  abundant, their approach is typically  surface-level, offering quick fixes  rather than long-term resolutions.
Keywords: Homeopathic; Indian; Origin